A screen-printing method for manufacturing of current collectors for structural batteries. Issue 3 (8th September 2021) - Johannisson, Wilhelm; Carlstedt, David; Nasiri, Awista; Buggisch, Christina; Linde, Peter; Zenkert, Dan; Asp, Leif E; Lindbergh, Göran; Fiedler, Bodo
Abstract: Structural carbon fibre composite batteries are a type of multifunctional batteries that combine the energy storage capability of a battery with the load-carrying ability of a structural material. To extract the current from the structural battery cell, current collectors are needed. However, current collectors are expensive, hard to connect to the electrode material and add mass to the system. Further, attaching the current collector to the carbon fibre electrode must not affect the electrochemical properties negatively or requires time-consuming, manual steps. This paper presents a proof-of-concept method for screen-printing of current collectors for structural carbon fibre composite batteries using silver conductive paste. Current collectors are screen-printed directly on spread carbon fibre tows and a polycarbonate carrier film. Experimental results show that the electrochemical performance of carbon fibre vs lithium metal half-cells with the screen-printed collectors is similar to reference half-cells using metal foil and silver adhered metal-foil collectors. The screen-printed current collectors fulfil the requirements for electrical conductivity, adhesion to the fibres and flexible handling of the fibre electrode. The screen-printing process is highly automatable and allows for cost-efficient upscaling to large scale manufacturing of arbitrary and complex current collector shapes. Hence, the screen-printing process shows a promising route to realization of high performing current collectors in structural batteries and potentially in other types of energy storage solutions.